Science Learning Model Based on Moral Value - Tahmid Sabri; FItria Arifiyanti (Journal of Educational Review and Research, 2018)
Moral value is essential to be instilled in students through learning in school. Therefore, it is necessary to study model in which there is emphasis moral value during learning, especially through science learning. Therefore, this study aims to develop a model of science-based science moral values in the hope of helping teachers to instill moral values in students. This study uses literature study method with reference sources in the form of books, scientific journals, and websites related to the development of science-based learning moral values.